The Value of Thematic Song Lyrics Character Education in 2013 Curriculum Books as a Praxis-Implementative Reference to Art Creation (Music) - Fitriani, Yulianti; Listiyani, Novi; Hadianda, Dedy Satya; Sentosa, Gempur (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2020)
This research was conducted because of the urgency of the need for a practical and practical reference to music creation that can be used by art creation students in carrying out the process of character development through thematic song lyrics contained in the 2013 curriculum book. On that basis, a strong foundation is needed to find values the value of character education in the lyrics of the songs is based on 18 character education values formulated by the Ministry of National Education (2010) consisting of; religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, national spirit, love for the motherland, respect for achievement, friendship, love for peace, love to read, care for the environment, care social and responsibility. The focus of research is focused on determining the character values that are reflected in the lyrics of thematic songs and obtaining a list of thematic songs along with the content of character education values that can be used as a reference in making music. The research method used is content analysis with a descriptive analytic approach. The results obtained in the form of an explanation of data analysis about the values of character education that appears from each song lyrics. So that it can be recommended to students of art creation to be able to consider the use of the value of character education found in the process of creating as a practical and practical reference